2008
DOI: 10.1021/bi702551c
|View full text |Cite
|
Sign up to set email alerts
|

The Helical Structure of Surfactant Peptide KL4 When Bound to POPC: POPG Lipid Vesicles

Abstract: KL 4 is a 21-residue peptide employed as a functional mimic of lung surfactant protein B which successfully lowers surface tension in the alveoli. A mechanistic understanding of how KL 4 affects lipid properties has proven elusive as the secondary structure of KL 4 in lipid preparations has not been determined at high resolution. The sequence of KL 4 is based on the C-terminus of SP-B, a naturally occurring helical protein that binds to lipid interfaces. The spacing of the lysine residues in KL 4 precludes the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 74 publications
1
26
1
Order By: Relevance
“…Lucinactant is a novel synthetic surfactant that contains KL 4 , a 21-amino acid peptide mimicking the function of surfactant protein B (SP-B). (13) The safety and effectiveness of lucinactant has been characterized in Phase 3 clinical trials for the prevention of RDS when administered as an intratracheal suspension. (14,15) Lucinactant may be uniquely suited for aerosolized delivery, as the KL 4 peptide contained in lucinactant is not susceptible to damage and inactivation during aerosolization.…”
Section: Introductionmentioning
confidence: 99%
“…Lucinactant is a novel synthetic surfactant that contains KL 4 , a 21-amino acid peptide mimicking the function of surfactant protein B (SP-B). (13) The safety and effectiveness of lucinactant has been characterized in Phase 3 clinical trials for the prevention of RDS when administered as an intratracheal suspension. (14,15) Lucinactant may be uniquely suited for aerosolized delivery, as the KL 4 peptide contained in lucinactant is not susceptible to damage and inactivation during aerosolization.…”
Section: Introductionmentioning
confidence: 99%
“…Resonances in these spectra can be assigned using NCACX and NCOCA experiments [6974], complemented by 13 C- 13 C [75, 76] and 13 C- 15 N correlation experiments [77]. Two-dimensional 13 C- 13 C correlation MAS spectra of Ail and OmpX in proteoliposomes (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Results at 14.1 T demonstrate that appreciable DNP enhancements are achieved throughout the lipid bilayer and that a DNP enhancement factor of 8.9 is achieved for KL 4 , a 21 residue amphipathic peptide which deeply partitions into the hydrophobic core region of lipid bilayers. Figure 1 shows a schematic of the sample preparation strategy using SL-lipids and the structure and depth of membrane partitioning of KL 4 , which has been previously characterized by NMR and EPR investigations [22][23][24][25] This particular combination of SL-lipids was chosen because the chemical connectivity and physical location of the radicals in each lipid species provides for close spatial proximity of the radicals while also enabling a perpendicular orientation between the g-tensors of the nitroxides. These are characteristics that emulate the properties of nitroxide biradicals, such as TOTAPOL, used in DNP experiments to date.…”
mentioning
confidence: 99%
“…The partitioning and structure of KL 4 is sensitive to both the degree of lipid acyl chain packing in proteoliposomes as well as pH. [22][23][24][25]31] The standard protocol for DNP sample preparation with water-soluble biradicals uses 60 % glycerol as a glassing agent in the solvent; however, it has been shown that small molecule cryoprotectants may alter the membrane environment. [7] Given that the SL-lipid system does not require or contain any glycerol, the inclusion of glycerol in the TOTAPOL system is likely changing the lipid acyl chain packing within the lipid bilayers and affecting the conformational equilibrium KL 4 adopts; alternatively differences in the pH or dielectric gradient at the lipid bilayer interface could be affecting the partitioning and ultimately the structure of the peptide.…”
mentioning
confidence: 99%
See 1 more Smart Citation